Sensory and Instrumental Flavor Changes in Green Tea Brewed Multiple Times - Lee, Jeehyun; Chambers, Delores; Chambers, Edgar, IV (My University, 2013)
Green teas in leaf form are brewed multiple times, a common selling point. However, the flavor changes, both sensory and volatile compounds, of green teas that have been brewed multiple times are unknown. The objectives of this study were to determine how the aroma and flavor of green teas change as they are brewed multiple times, to determine if a relationship exists between green tea flavors and green tea volatile compounds, and to suggest the number of times that green tea leaves can be brewed. The first and second brews of the green tea samples provided similar flavor intensities. The third and fourth brews provided milder flavors and lower bitterness and astringency when measured using descriptive sensory analysis. In the brewed liquor of green tea mostly linalool, nonanal, geraniol, jasmone, and β-ionone volatile compounds were present at low levels (using gas chromatography-mass spectrometry). The geraniol, linalool, and linalool oxide compounds in green tea may contribute to the floral/perfumy flavor. Green teas in leaf form may be brewed up to four times: the first two brews providing stronger flavor, bitterness, and astringency whereas the third and fourth brews will provide milder flavor, bitterness, and astringency.
Citation: Lee, J., Chambers, D., & Chambers, E. (2013). Sensory and Instrumental Flavor Changes in Green Tea Brewed Multiple Times. Foods, 2(4), 554–571. https://doi.org/10.3390/foods2040554
Keywords: Flavor; Green Tea; Multiple Brews; Sensory; Volatile Compounds